Determination of platinum, palladium and rhodium, in aqueous media by means of reversed phase-high performance liquid chromatography (RP-HPLC) after complexation with N,N-dialkyl-N'-acylthioureas - Mautjana, Nare Alpheus (Department of Chemistry, 2015)
Includes bibliographical references.